CAG repeat polymorphism in androgen receptor and infertility: A case-control study - Shiva Sharestani; Seyed Mehdi Kalantar; Nasrin Ghasemi; Ehsan Farashahi Yazd (Shahid Sadoughi University of Medical Sciences, 2021)
Abstract Background: Androgens play a role in the development of male phenotype and spermatogenesis during puberty, the function of which is regulated by the androgen receptor (AR) gene. There is a polymorphism site in exon 1 of the gene encoding this receptor that can have different frequencies of CAG trinucleotide repeats and leads to the formation of polyglutamine chains of different lengths in the N-terminal domain of the AR protein and reduced sperm production by affecting spermatogenesis. Objective: To investigate whether the cause of a group of unexplained infertilities could be the increased frequency of CAG repeats in the AR gene of patients with oligozoospermia and azoospermia. Materials and Methods: In this case-control study, 84 men including 42 with unexplained infertility As a case group and 42 fertile men as a control group were selected. The frequency of CAG repeats was determined by the polymerase chain reaction method and then the difference in the frequency of these repeats was determined based on the difference in band size on the agarose gel. Results: The mean CAG repeat length in the azoospermia and oligozoospermia group was 17.5 ± 0.63 and in the fertile group it was 16.11 ± 0.75 (p = 0.46). In addition, most men (88.1% in the case group and 71.41% in the control group) had 13-23 repeats. Conclusion: No significant correlation was found between CAG repeat length and the risk of male factor infertility in an ethnically defined population of Iranian men. The role of regulatory factors and epigenetic changes should be taken into account too.